Territorio de la memoria - Albero Muñoz, María Del Mar (EDITUM. Ediciones de la Universidad de Murcia, 2025)
These studies are a selection of those presented and discussed at the I National Congress of Young Historians, meeting scientist held in Murcia in February 2014. There, and under the premises of the debate and exchange of the exchange of theKnowledge, these visions were raised around a territory and a memory, the acute need experienced by peoples to have a clear awareness of their history and cultural heritage as a fundamental weapon to combat all kinds of decks, manipulations andTo¿picos, so frequent in these times. This first Congress aimed to investigate various aspects of the articosic history of Levante Español, particularly in the area of ​​Murcia, but the proposition of the organizers has been and is not limited exclusively to local,but to give a greater breadth of view to the works that constitute the contributions of future congresses. The idea of ​​summoning Young Researchers who, recise their degree of Art History, try to make their first weapons in the field of research, seems excellent and essential, so much as much as much as soon asthat the current circumstances make difficult to see those works published that sometimes by excessive bison, do they seem to lack interest, which may be true; But when these young researchers are closed from the beginning, the danger of definitively abandoning a path for which they have already received a good formation that in the future can become an authentic intellectual maturity that Driving high -draft publications.